CAROTENOIDS FROM PLANTS USED IN DIETS FOR THE CULTURE OF THE PACIFIC WHITE SHRIMP (Litopenaeus vannamei) - J. T. Ponce-Palafox (Revista Mexicana de Ingeniería Química, 2006)
The use of carotenoids as pigments in aquaculture diets is well documented. These pigments seem to have manyphysiological functions that include a role as antioxidant and provitamin A. A common characteristic of shrimpsis their pink flesh when cooked. Dietary carotenoids, among them astaxanthin, are the responsible for the ability ofcaptured shrimps for developing their characteristic color when cooked. These carotenoids are sourced mainly fromkrill and phytoplankton. However, for cultured shrimps carotenoids are not available unless included in their feeds.The current limited production of astaxanthin cannot meet the growing demand for this pigment, so that scientistshave strived to find new alternative sources for this pigment. Carotenoids from plant sources seem to provide aninteresting option to this problem. The present study is aimed at showing the state of the art in the research on the useof pigments from plant extracts and their potential for their incorporation in the feed of shrimps (Litopenaeusvannamei). Some promising alternative plant sources for the pigment astaxanthin are the carotenoids from the yeastPhaffia rhodozyma, the microalgae Haematococcus pluvialis, Dunaliella salina and Spirulina , the petals fromAdonis aestivalis and Tagetes erecta, the red chili bells from Capsicum annuum and the leguminous Leucaenaleucocephala. Many of these carotenoids sources have been used at concentrations of 100 to 450 mg/kg in the diet ofshrimps, and in particular for the white shrimp (L. vannamei), a marked increase of carotenoid content in theexoskeleton and abdomen has been observed. This suggests that the different carotenoids contained in plant extractssuch as zeaxanthin, lutein and capsanthin are converted into astaxanthin.